Development of Website-Based Social Teaching Material in Elementary School - Hanifah, Nur Hidayah; Putri, Candra Avista; Salsabila, Helga; Megawangi, Ratna; Hurriyah, Siti Mar’atul Eva (JIP Jurnal Ilmiah PGMI, 2023)
This study aims to develop web-based teaching materials social in elementary schools and determine the effectiveness of student learning outcomes. This research uses a research and development model developed by ADDIE consisting of five stages, namely Analysis, Design, Development, Implementation, Evaluation. The test subject of this study was MI grade IV student Nurul Jadid Blitar. Data collection techniques use observation, interviews, questionnaires, tests and documentation. Analysis of product effectiveness using independent t-test.  The results of the research were the development of web-based teaching materials getting material expert validation of 95% with very valid criteria, design expert validation of 89% with very valid criteria, and learning expert validation of 92.7% with very valid criteria. Student learning outcomes have increased, namely the average pretest score in the experimental class 52.5, then in the experimental class treatment using web-based teaching materials, the average value of the postest is 82.5 The results of the independent t-test show a value of 0.008, so it can be interpreted that there is an influence of the use of website-based learning media on student learning outcomes. So it can be said that the use of web-based teaching materials has an influence on improving student learning outcomes and is used in the learning process.